Creating digital video in your school how to shoot, edit, produce, distribute, and incorporate digital media into the curriculum - Bell, Ann 1945- (Gale virtual reference library, 2005)
Guide for teachers and media specialists to help students increase their visual literacy, particularly media literacy and information literacy.